Climatic change in Central Asia during MIS 3/2: a case study using biological responses from Lake Baikal - Swann, George E.A.; Mackay, Anson W.; Leng, Melanie J.; Demory, Francois (Elsevier, 2005)
A Marine Isotope Stage (MIS) 3/early MIS 2 section from a structural high along the east coast of the North Basin of Lake Baikal was analysed for diatoms, C/N ratios, and organic carbon isotope ratios. Diatoms were present throughout MIS 3 and early MIS 2, with high concentrations of the planktonic taxa Cyclotella sp. c.f. gracilis between 54 and 51.5 kyr BP indicating relatively warm, interstadial, conditions. Following a %TOC inferred climatic cooling between 43.2 and 39.1 kyr BP, evidence of a more muted δ13C(organic) and %TOC inferred climatic warming from c. 39.1–34.7 kyr BP coincides with a period of very high diatom concentrations, indicating high aquatic productivity, at the Buguldeika Saddle in the South Basin of Lake Baikal. No evidence exists for a ‘Kuzmin’ catchment erosional event in the North Basin during MIS 3. This, however, may reflect the location of the coring site away from major riverine inputs. Abrupt climatic cooling at the culmination of both warm phases in the North Basin are associated, on the basis of the palaeomagnetic age-model and correlations to existing sites in Lake Baikal, with the initiation of Heinrich events 5 (c. 50 kyr BP) and 4 (c. 35 kyr BP), respectively, in the North Atlantic. The amount of organic material declines across the MIS 3/MIS 2 transition while constant C/N ratios suggest organic material to be predominantly derived from phytoplankton. An increase in δ13C(organic) at the MIS 3/MIS 2 transition may therefore indicate changes in aquatic productivity, pCO2 or the inorganic carbon pool.